An Analysis of an Intelligent Chatbot Using Natural Language Processing (International Journal of Food and Nutritional Sciences, 2022)
Natural language processing (NLP) is a subject of languages, computer programming, and artificial intelligence concerned with computer-human language interactions, specifically how to train computers to process and evaluate huge volumes of natural language data. The objective is to create a computer that can "understand" the contents of papers, including the contextual subtleties of the language contained within them. The system can then extract information and insights from the papers, as well as classify and arrange the documents themselves. Chatbots are becoming more popular as computer communication applications. Some programs react intelligently as if they were humans. This sort of application is known as a Chatbot. This study provides a high-level review of cloud-based chatbot technology, as well as chatbot programming and the programming issues that exist in the modern and future chatbot eras. The development and deployment of a Chatbot system are also the focus of this investigation. The author would also examine other use cases and design strategies for Chatbots.